Fatty Acids Support the Fitness and Functionality of Tumor-Resident CD8+ T Cells by Maintaining SCML4 Expression - Feng, Maoxiao; Liu, Xiaoyan; Hao, Xiaodong; Ren, Yidan; Dong, Guoying; Tian, Jie; Wang, Yuli; Du, Lutao; Wang, Yunshan; Wang, Chuanxin (Cancer research (Chicago, Ill.), 2023)
CD8+ tissue-resident memory T (Trm) cells and tumor-infiltrating lymphocytes (TIL) regulate tumor immunity and immune surveillance. Characterization of Trm cells and TILs could help identify potential strategies to boost antitumor immunity. Here, we found that the transcription factor SCML4 was required for the progression and polyfunctionality of Trm cells and was associated with a better prognosis in patients with cancer. Moreover, SCML4 maintained multiple functions of TILs. Increased expression of SCML4 in CD8+ cells significantly reduced the growth of multiple types of tumors in mice, while deletion of SCML4 reduced antitumor immunity and promoted CD8+ T-cell exhaustion. Mechanistically, SCML4 recruited the HBO1-BRPF2-ING4 complex to reprogram the expression of T cell-specific genes, thereby enhancing the survival and effector functions of Trm cells and TILs. SCML4 expression was promoted by fatty acid metabolism through mTOR-IRF4-PRDM1 signaling, and fatty acid metabolism-induced epigenetic modifications that promoted tissue-resident and multifunctional gene expression in Trm cells and TILs. SCML4 increased the therapeutic effect of anti-PD-1 treatment by elevating the expression of effector molecules in TILs and inhibiting the apoptosis of TILs, which could be further enhanced by adding an inhibitor of H3K14ac deacetylation. These results provide a mechanistic perspective of functional regulation of tumor-localized Trm cells and TILs and identify an important activation target for tumor immunotherapy.CD8+ tissue-resident memory T (Trm) cells and tumor-infiltrating lymphocytes (TIL) regulate tumor immunity and immune surveillance. Characterization of Trm cells and TILs could help identify potential strategies to boost antitumor immunity. Here, we found that the transcription factor SCML4 was required for the progression and polyfunctionality of Trm cells and was associated with a better prognosis in patients with cancer. Moreover, SCML4 maintained multiple functions of TILs. Increased expression of SCML4 in CD8+ cells significantly reduced the growth of multiple types of tumors in mice, while deletion of SCML4 reduced antitumor immunity and promoted CD8+ T-cell exhaustion. Mechanistically, SCML4 recruited the HBO1-BRPF2-ING4 complex to reprogram the expression of T cell-specific genes, thereby enhancing the survival and effector functions of Trm cells and TILs. SCML4 expression was promoted by fatty acid metabolism through mTOR-IRF4-PRDM1 signaling, and fatty acid metabolism-induced epigenetic modifications that promoted tissue-resident and multifunctional gene expression in Trm cells and TILs. SCML4 increased the therapeutic effect of anti-PD-1 treatment by elevating the expression of effector molecules in TILs and inhibiting the apoptosis of TILs, which could be further enhanced by adding an inhibitor of H3K14ac deacetylation. These results provide a mechanistic perspective of functional regulation of tumor-localized Trm cells and TILs and identify an important activation target for tumor immunotherapy.SCML4 upregulation in CD8+ Trm cells and tumor-infiltrating lymphocytes induced by fatty acid metabolism enhances antitumor immune responses, providing an immunometabolic axis to target for cancer treatment. See related commentary by Chakraborty et al., p. 3321.SIGNIFICANCESCML4 upregulation in CD8+ Trm cells and tumor-infiltrating lymphocytes induced by fatty acid metabolism enhances antitumor immune responses, providing an immunometabolic axis to target for cancer treatment. See related commentary by Chakraborty et al., p. 3321.